Cooking Beliefs and Culinary Program Interest of College Students with Overweight and Obesity from Different Environments (P21-012-19). (13th June 2019) - Mahmood, Miriam; Kleiman, Jennifer; Ryan, Rachel; Wong, Kayla; Lu, Ronald; Chen, Yufei; Bodas, Devika; Haisley, Quinn; Abdelmassih, Kelly; Fernandes, Nicolle; Bihuniak, Jessica
Abstract: Objectives: College students with overweight/obesity previously reported a lack of confidence in meal planning/production, which may contribute to current weight status and subsequent weight gain. The objectives of this study were to: 1) determine cooking beliefs of students with overweight/obesity from different environments and 2) assess interest in a culinary-focused, weight loss program. Methods: Students with overweight or obesity (BMI > 25), ages 18–24, enrolled in New York University (NYU) or LaGuardia Community College (LCC) were recruited. Participants completed a Qualtrics survey that included: 1) Cooking Attitudes Subscale, 2) Cooking Behaviors Subscale, 3) Cooking Self-Efficacy Scale (SEC), 4) Self-Efficacy for Using Basic Cooking Techniques Scale (SECT) and 5) a culinary program preference questionnaire. Height and weight were objectively measured. Descriptive, Chi square, Kruskal-Wallis, and post hoc Dunn test statistics were conducted. Results: Students ( N  = 91; 19.6 ± 1.6 years; BMI 31.7 ± 5.6) were 64% female and 24% non-Hispanic. Institution type was associated with ethnicity ( P  = 0.03), with a higher percentage of non-Hispanic students from NYU. NYU students had a significantly lower BMI ( P  = 0.01) and were younger ( P  = 0.005). There was a significant difference in the Cooking Behaviors Subscale between institutions, with NYU students having overall lower scores ( P  = 0.0001). For LCC, there was a significant difference in BMI between the lowest and third quartiles of SECT scores ( P  = 0.04); students with a higher BMI had lower scores. At NYU, there was a significant difference in BMI between the lowest and second ( P  = 0.004) and third ( P  = 0.01) quartiles of the Cooking Behaviors Subscale; the lowest quartile had a higher mean BMI. Regardless of institution, the majority of students were interested in participating in a culinary-focused weight loss program for 6–8 weeks. However, NYU students reported a greater interest in weekly group meetings ( P  = 0.0001). Conclusions: There is heterogeneity in cooking beliefs by college environment and BMI. However, interest in a culinary-focused, weight loss program is high for both 2- and 4-year tertiary institution students with overweight/obesity. Focus groups will be used for the development of population specific interventions. Funding Sources: NYU College of Arts and Science Dean's Undergraduate Research Fund Grant (Spring 2018).